Efficient liability law when parties genuinely disagree - Luigi Alberto Franzoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
This article compares the classic liability rules, negligence and strict liability, under the hypothesis that injurers and victims formulate subjective beliefs about the probabilities of harm. Parties may reasonably disagree in their assessment of the precautionary measures available: a measure regarded as safe by one party may be regarded as not safe by the other. By relying on the notions of Pareto effi ciency and "No Betting" Pareto effi ciency, the article shows that negligence is the optimal liability rule when injurers believe that the probability of harm is always higher than the victims do, while strict liability with overcompensatory damages is the optimal rule in the opposite case. The same results apply to bilateral accidents and, speciÖcally, to product-related harms in competitive markets. Overcompensatory ("punitive") damages provide consumers with insurance against their own pessimism.
Keywords: 330; negligence vs. strict liability; products liability; scientiÖc uncertainty; No Betting Pareto Dominance